CO2‐induced crystal engineering of polylactide and the development of a polymeric nacreous microstructure. Issue 11 (10th July 2017) - Sankarpandi, Sabapathy; Park, Chul B; Ghosh, Anup K
Abstract: Nacre's biomineralization process and its self‐organizing brick‐and‐mortar crystalline microstructure have inspired many researchers to develop new materials derived from the natural world. In our study, we took a novel approach to two‐dimensional (2‐D) crystallization. That is, we applied the biomineralization self‐organizational principle that exists in natural materials to a biopolymer (polylactide). The CO2 ‐induced crystallization of poly(d ‐lactide), with its unique diffusion‐controlled crystallization mechanism, tends to produce distinct 2‐D spherulitic structures. We found that these 2‐D spherulites were self‐organizing in nature, and that they created a stack of 2‐D spherulitic structures. These crystalline microstructures, with their intervening amorphous phase, were foamed in situ due to the CO2 ‐induced crystallization self‐exclusion phenomenon. We compared the resultant crystalline structure with nacre's brick‐and‐mortar crystalline microstructure to confirm the biomimetic principle of self‐organization. To the best of our knowledge, this is the first time that a biopolymer has been crystallized in a 2‐D manner in a way that resembles nature's biomineralization process. The hierarchical crystalline microstructure is morphologically similar to that of nacre biomaterials. This novel crystallization technique is simple, absolutely non‐toxic and works swiftly to produce a brick‐and‐mortar crystalline microstructure with a high degree of order. © 2017 Society of Chemical Industry Abstract : The novelty of the current paper lies in the development of a hard and tough polymeric nacreous (brick‐and‐mortar) microstructure via instantaneous two‐dimensional crystallization and in‐situ foaming approach using high‐pressure CO2 .